An exploration of the role of the clinical academic and strategies to sustain and build the clinical academic workforce - Burke, Elaine (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2022)
Background Clinical academics are critical to delivering high quality patient care and discovering new ways to treat disease (1), however the clinical academic workforce is shrinking (2-4). There is a need to clearly define the role and attributes of successful clinical academics, and to investigate strategies to maintain this workforce. Methodology A concept analysis of the term ?clinical academic? was carried out using the Walker and Avant framework. Following this, 10 clinical academics at different career stages were interviewed on their construal of successful clinical academic practice using a structured interview technique, Repertory Grid. The data was analysed quantitatively and qualitatively. Social Cognitive Career Theory provided a framework for interpreting results. A combined clinical academic training programme for junior doctors at the earliest career stage, the Academic Internship Track (AIT) is described. This programme was evaluated using the CIPP model (Context, Input, Process and Products). A resum? study of applications to the AIT over 4 years was conducted to monitor gender balance and the effects of anonymising applications. Results The ideal clinical academic is highly motivated and embodies attributes such as innovation, perseverance, integrity, and collaboration. Maintenance of the role requires appropriate training, a supportive work environment and adequate investment. Consequences include benefits for patients, students, and clinicians. Development of supports for clinical academics should take personal and organisational factors into consideration as well as learning experiences and person-environment fit. There is a demand for early career combined clinical academic training; participants in the AIT contribute substantially to their field, and the programme may contribute to retention of this talent in Ireland. Anonymising applications to the AIT did not result in statistically significant differences in scores, however gender balance improved. Cues for control may play an important role in mitigating unconscious bias.
APPROVED
Keywords: Clinical Academic; Medical Education; Clinician Scientist; Concept Analysis; Repertory Grid Technique; CIPP model of evaluation; Resume study; Gender equality; Postgraduate medical training; Medical careers